2019
DOI: 10.1186/s41938-019-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis kurstaki strains produce vegetative insecticidal proteins (Vip 3) with high potential

Abstract: Bacillus thuringiensis (Bt) produces vegetative insecticidal proteins (Vip) during its vegetative growth stage. Vip3 proteins have a significant role in insecticidal activity of this bacterium. Each new bacterial isolate may encode Vip with different significance. The Vip protein coding by vip genes of two Bt strains (BnBt and MnD) with high insecticidal activity was characterized in this study. Polymerase chain reaction (PCR)-based screening for Vip genes of these Bt isolates expressed the detected Vip gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…compared with Vip3Aa16 [ 85 ]. In another study, two Bt strains, BnBt and MnD, were found to produce Vip proteins in isolates of great potential with a high toxicity (LC 50 = 41.860 ng/μL of BnBt and 55.154 ng/μL of MnD) in the second instar larvae of S. littoralis [ 86 ]. Lone and co-workers isolated and expressed a novel Vip3Aa61 gene in Escherichia coli from isolate B. thuringiensis JK37.…”
Section: Identification Of Bt Isolates Containing Vip Genesmentioning
confidence: 99%
“…compared with Vip3Aa16 [ 85 ]. In another study, two Bt strains, BnBt and MnD, were found to produce Vip proteins in isolates of great potential with a high toxicity (LC 50 = 41.860 ng/μL of BnBt and 55.154 ng/μL of MnD) in the second instar larvae of S. littoralis [ 86 ]. Lone and co-workers isolated and expressed a novel Vip3Aa61 gene in Escherichia coli from isolate B. thuringiensis JK37.…”
Section: Identification Of Bt Isolates Containing Vip Genesmentioning
confidence: 99%
“…The 90 kDa Vip3 protein was expressed and showed 10th-day mortality of 86.66% (Bn Bt ) and 83.33% (MnD) in comparison to 13.33% in control larvae against the second instar stage of S. littoralis . The LC 50 values were obtained as 55.15 and 41.86 ng/μl for MnD and Bn Bt , respectively ( Güney et al, 2019 ). The assessment of the potential of Vip3 protein against whiteflies was done through isolation of complete coding sequence (2.4 kb) of gene from an isolate of Egypt.…”
Section: Vegetative Insecticidal Proteins (Vips)mentioning
confidence: 99%
“…Spodoptera littoralis larvae were reared on artificial diet under the laboratory conditions of 25 ± 1 °C and 65 ± 5% (Güney et al 2019). Emerged adults were fed on honey solution in impregnated cotton in plastic boxes (36 × 23 cm).…”
Section: Rearing Of Spodoptera Littoralis Larvaementioning
confidence: 99%